Characterization of the stimulating effect of low-dose stressors in maize seedlings - Nyitrai, Péter (Acta Biologica Szegediensis, 2002)
The effect of some more or less harmful compounds like Cd, Pb, Ni, Ti salts and DCMU at low concentrations on the development of chloroplasts in maize seedlings has been investigated. Stimulation of chlorophyll (Chl) synthesis, photosynthetic activity and increased amount of photosystem I and light-harvesting complex II (LHCII) was observed during the treatment, while chlorophyll a/b ratios did not change considerably except in DCMU treated plants. Electron micrographs showed only sligth differences in the morphology of chloroplast lamellar system. It is assumed that these low-dose stressors generate non-specific alarm reactions in plants, which may involve changes of the hormonal balance.